Banditry and subversion in Croatia at the end of the long nineteenth century - Pejić, Luka (Études sur la Région Méditerranéenne, 2020)
The gradual decline of the Austro-Hungarian political power during the last phase of the First World War consequently led to the collapse of its, previously solidly established, repressive mechanisms. On one hand, mass mobilization of police officers that were sent to the battlefield raised a question of public security and increasing crime rates in some cities, including those in Croatia. For example, according to certain data, almost 70% of policemen from Osijek were recruited by the military when the war broke out. Moreover, scarcity of the working force and different provisions affected general productivity, while lack of certain materials, such as paper, posed a great challenge to authorities in their attempt to establish an effective communication network with their subordinates, or print new legal regulations. Wave of socialist revolutions in Europe (Russia, Germany, Hungary) undoubtedly made a significant impact on some members of the Croatian society between 1917 and 1919. Following the decades of ideological and organizational development of the domestic labor movement, some Croatian activists actively supported or even participated in the communist uprising in Russia and Béla Kun’s Hungarian Soviet Republic at the very end of the long 19th century. It is fascinating that several attempts were made to form short-lived socialist republics on the Croatian or neighboring Hungarian territory. Concerning that, the return of soldiers from the Eastern Front, where they were exposed to the Bolshevik ideology, made the distribution of such subversive ideas even stronger. As it became clear that the war defeat was inevitable, while the concept of a new South Slavic state was getting closer to its political realization, defection hit the Monarchy’s army en masse. Groups of army deserters and other radicalized individuals, known as “Green Cadres” (zeleni kadar), took part in collective banditry that lasted for years in Croatia-Slavonia. This presentation will question the correlation between the collapse of the Monarchy’s repressive mechanisms during the period of significant sociopolitical transformation and the spread of subversive socialist ideas as well as banditry, using the Croatian context as a specific case study.